Efficacy and safety of corticosteroids prophylaxis in cardiac surgery: A protocol for systematic review and meta-analysis. Issue 50 (11th December 2020) - He, Jian; Zhang, Yuling; Qiu, Zhihuang; Chai, Tianci; Fang, Guanhua; Hu, Yunnan; Xu, Fan; Huang, Qiuyu; Zheng, Hui; Zhou, Hao; Tian, Mengyue; Chen, Liang Wan
Abstract: Background: Although corticosteroid prophylaxis in adult cardiac surgery has been studied extensively for 40 years, its role remains controversial, and the optimal dose remains uncertain. The objective of this meta-analysis was to estimate the clinical benefits and risks of corticosteroid use in cardiopulmonary bypass. Methods: We will search Pubmed, Web of Science, Embase, Clinical Trials, and Cochrane Central Register of Controlled Trials for relevant clinical trials published in any language before August 1, 2020. Randomized controlled trials (RCTs) of interest which meet inclusion criteria published or unpublished will be included. We will divide the included studies into child and adult groups for analysis. If sufficient data are available, the included trials will be divided into 4 subgroups: ⩽20 mg/kg (low dose), 20–40 mg/kg (slightly high dose), 40–100 mg/kg (high dose), and >100 mg/kg (ultra high dose) based on the equivalent hydrocortisone dose. INPLASY registration number: INPLASY2020100044. Results: The results of this study will be published in a peer-reviewed journal. Conclusion: This study will compare the efficacy of tprophylactic corticosteroids for adults and children undergoing cardiac surgery with CPB. Due to the nature of the disease and intervention methods, randomized controlled trials may be inadequate, and we will carefully consider inclusion in high-quality, non-randomized controlled trials, but this may result in high heterogeneity and affect the reliability of the results.